PENGEMBANGAN KULIT PANGSIT MENJADI PANGSIT ROLL LUMER BERBAGAI VARIAN RASA BY SUJAJEMI - Rodhatul Jannah; Febri Ariyantiningsih; Jeny Dwi Anwar; Susan Melia (Fakultas Ekonomi dan Bisnis, 2025)
Pangsit roll lumer is an innovative food product that transforms traditional dumpling wrappers into a modern snack with flavor varieties applied on the outside, such as chocolate, matcha, and tiramisu. This study aims to analyze the product development process, sensory evaluation, and market competitiveness assessment of pangsit roll lumer. The methods employed include production, observation, and interviews. The results indicate that pangsit roll lumer with chocolate, matcha, and tiramisu flavors received positive responses from consumers in terms of taste, aroma, color, and texture. Physicochemical analysis shows that the product remains safe for consumption and has high economic value and market competitiveness. This innovation opens opportunities for the development of snack industries based on traditional foods and can inspire other MSMEs to create innovative and competitive products.